'Moringa oleifera: study of phenolics and glucosinolates by mass spectrometry'†. (10th September 2014) - Maldini, Mariateresa; Maksoud, Salwa A.; Natella, Fausta; Montoro, Paola; Petretto, Giacomo Luigi; Foddai, Marzia; De Nicola, Gina Rosalinda; Chessa, Mario; Pintore, Giorgio; Giorgi, Gianluca
<x xml:space="preserve">Abstract</x> Moringa oleifera is a medicinal plant and an excellent dietary source of micronutrients (vitamins and minerals) and health‐promoting phytochemicals (phenolic compounds, glucosinolates and isothiocyanates). Glucosinolates and isothiocyanates are known to possess anti‐carcinogenic and antioxidant effects and have attracted great interest from both toxicological and pharmacological points of view, as they are able to induce phase 2 detoxification enzymes and to inhibit phase 1 activation enzymes. Phenolic compounds possess antioxidant properties and may exert a preventative effect in regards to the development of chronic degenerative diseases. The aim of this work was to assess the profile and the level of bioactive compounds in all parts of M. oleifera seedlings, by using different MS approaches. First, flow injection electrospray ionization mass spectrometry (FI‐ESI‐MS) fingerprinting techniques and chemometrics (PCA) were used to achieve the characterization of the different plant's organs in terms of profile of phenolic compounds and glucosinolates. Second, LC‐MS and LC‐MS/MS qualitative and quantitative methods were used for the identification and/or determination of phenolics and glucosinolates in M. oleifera. Copyright © 2014 John Wiley & Sons, Ltd.